(untitled) (Revista Científica Integrada, 2025)
Objective: To analyze the components of the health care network for people with high blood pressure in Piauí, Brazil, and their association with the attribute of comprehensiveness of Primary Health Care through the National Health Survey. Methods: A descriptive cross-sectional study, using secondary data from the 2019 National Health Survey, analyzed 147 people aged 18 or over, residing in Piauí and diagnosed with high blood pressure, using module H (medical care) of the National Health Survey, with data collection between February and March 2023; sociodemographic and comprehensiveness of Primary Health Care variables were evaluated, using descriptive, bivariate statistics and logistic regression. Results: There was no association between sociodemographic variables and the comprehensiveness of the services available and provided. For the comprehensiveness of the services available, paying for one’s medication stood out as a risk factor, and the chances of having comprehensive services provided increased among users who obtained their medication through the “aqui tem farmácia popular” (popular pharmacy here) through integrative and complementary care practices. The results highlight the importance of considering the operational structure of the health care network when planning and organizing services for people with hypertension. Conclusion: The study revealed that paying for hypertension medications can harm the comprehensiveness of PHC services, but the Brazilian Popular Pharmacy Program and integrative practices improved care, highlighting the need for more research to improve the RAS and health policies.